CONTRIBUTIONS OF CREATIVE INTELLECTUALS IN THE FIELD OF SCIENCE TO THE FIELD OF EDUCATION IN THE YEARS OF INDEPENDENCE - Bokiyev Bakhrom Uktamovich (Galaxy International Interdisciplinary Research Journal, 2022)
Since ancient times, all fields of science, especially astronomy, mathematics, medicine, chemistry, architecture, mineralogy, philosophy, music, linguistics, and literature have been developed in Central Asia, especially in Uzbekistan. Nowadays, scientists of Uzbekistan have enriched the scientific heritage created by their ancestors.